A flexible and implantable piezoelectric generator harvesting energy from the pulsation of ascending aorta: in vitro and in vivo studies. (March 2015) - Zhang, Hao; Zhang, Xiao-Sheng; Cheng, Xiaoliang; Liu, Yang; Han, Mengdi; Xue, Xiang; Wang, Shuaifei; Yang, Fan; A S, Smitha; Zhang, Haixia; Xu, Zhiyun
Abstract: This research is aimed to evaluate the feasibility and efficacy of generating electric power utilizing the pulsating energy of ascending aorta with a flexible and implantable piezoelectric generator (PG) through in vitro and in vivo studies. In the in vitro study, the max output voltage ( V max), current ( I max) and power ( P max) of the PG were 10.3 V, 400 nA and 681 nW respectively. The quantity of electric charging by one pulse was about 7–9 nC. Factors affecting its output performance were investigated with single variable experiments. We further implanted the PG to wrap around the ascending aorta of a porcine to investigate the output performance in vivo. The V max and I max of the implanted PG were 1.5 V and 300 nA under the heart rate of 120 bpm and the blood pressure of 160/105 mmHg. The instantaneous output power was 30 nW with a long-lasting duration of 700 ms and 77.8% duty ratio. The implanted PG could charge for a 1 μF capacitor to 1.0 V within 40 s. Graphical abstract: The power supply of current implantable electronic devices relies on batteries, which have to be replaced surgically after depletion. In contrast, continuing energy output from human cardiovascular system has not been fully utilized up to now. The goal of the present study was to test the feasibility and efficacy of generating electric power utilizing the pulsating energy of ascending aorta with a flexible and implantable piezoelectric generator (PG). Highlights: This article demonstrates the feasibility and efficacy of generating electric power utilizing the pulsating energy of ascending aorta with a flexible and implantable piezoelectric generator (PG). A PG made of flexible piezoelectric polymer (i.e., PVDF) was well-designed with the biocompatible polyimide package, and it was systematically studied in vitro and in vivo from four aspects, including external load effect, flow pressure effect, size effect and its charging ability. With a PG of 56 mm×25 mm×200 μm, a max power density of 170 nW/cm 3 was achieved in vitro study, while in vivo study the PG showed the attractive working ability to charge a 1 μF capacitor to 1.0 V within 40 s.